Oral analogues of GLP-1: perspectives on glycemic control and cardiorenal risk in patients with type 2 diabetes mellitus (2024)
At present, type 2 diabetes mellitus (T2DM) is the leading cause of end-stage kidney disease. The management of T2DM in recent years has moved from a glucocentric approach to a global approach with the priority of introducing treatments that offer renal and cardiovascular protection. In this article, we review in depth the pharmacokinetics and pharmacodynamics of the first oral analog of glucagon-like peptide-1 (oral semaglutide) in comparison with its subcutaneous formulation. The knowledge and implementation of these drugs will be very useful in daily clinical practice